Gastroprotective effect of SKM-Gelcocid suspension on indomethacin induced gastric ulcer in female Wistar rats - Ganesh Thangavel; Tharani Mohanasundaram; Vadivelan Ramachandran (Elsevier, 2024)
Background: Peptic ulcer causes painful ulcers or lesions in the stomach or duodenum. It is also known as a gastric ulcer, which is damage to the gastric wall or lower portion of the esophagus. In the allopathic system, many medications such as H2 receptor antagonists, and anti-H. pylori, proton pump inhibitors, and others with rapid therapeutic activities were utilized to treat peptic ulcers.Purpose: The main aim of this work is to report an in-vivo gastro protective investigation of Saminathapuram Karuppana Gounder Maeilanandhan- Gelcocid suspension (SKM-GS), an Ayurveda formulation, using indomethacin-induced gastric ulcer rats.Study Design and Methods: In the present study we have reported the gastroprotective effect of SKM-GS, an Ayurveda formulation. Indicators such as gastric ulcer area, ulcer index, gastric wall mucus, non-protein sulfhydryl groups (NP-SH), and anti-oxidant enzymes secreted by treatment with SKM-GS on Indomethacin-induced ulcers in female Wistar rats.Result: The results showed a significant (p>0.001) reduction in gastric ulcer area, ulcer index, and an increase in ulcer preventive index. It further revealed an increase in gastric wall mucus and NP-SH secretion. Treatment with SKM-GS showed decreased levels of malondialdehyde (MDA) levels and increased levels of glutathione (GSH) and glutathione peroxidase (GPx) enzymes in the indomethacin-induced gastric ulcer rats. Female Wistar rats when treated with 200 mg/kg and 400 mg/kg of SKM-GS identical to Lansoprazole (Lanso) showed an increase in gastroprotective activity in a dose-dependent manner.Conclusion: The SKM-GS's gastro-protective properties were similar to the well-known anti-ulcer, Lansoprazole. These effects may be due to antioxidant activity.